Biological tunable photonics: Emerging optoelectronic applications manipulated by living biomaterials. (November 2021) - Zhang, Yifan; Wang, Ziyihui; Chen, Yu-Cheng
Abstract: Over the past few decades, optoelectronic devices have played a key role in human life and modern technology. To meet the development trends of the industry, photonics with tunable functions have emerged as building blocks with immense potential in controlling light–matter interactions, sensors, and integrated photonics. Compared with artificially designed materials and physical approaches, stimuli-responsive biointerfaces enable a higher level of functionalities and versatile means to tailor optical responses at the nanoscale. Recent advances in biological tunable photonics have attracted tremendous attention owing to the incorporation of living biomaterials into organic photonic and photoelectric devices. In this review, we highlight the advances made in biological tunable photonics during the past five years. We begin with an overview of the competency of natural biological materials, followed by the introduction of key stimuli that have a dominant influence on the development of active biointerfaces. Lastly, we present a comprehensive summary of optoelectronic applications that utilize living biomaterials as active controls. Such applications include bioactivated light-emitting diodes, biological lasers, active plasmonics, robotics, biological logic gates, light-harvesting antennas, molecular photonic wires, bioenergy, and biophotovoltaics. The opportunities and challenges for future research directions are also briefly discussed.